Health-related quality of life determinants in survivors of a mass methanol poisoning outbreak: six-year prospective cohort study. (1st September 2020) - Rulisek, Jan; Waldauf, Petr; Belohlavek, Jan; Balik, Martin; Kotikova, Katerina; Hlusicka, Jiri; Vaneckova, Manuela; Seidl, Zdenek; Diblik, Pavel; Bydzovsky, Jan; Heissigerova, Jarmila; Urban, Pavel; et al.
Abstract: Purpose: The effect of acute methanol poisoning on the follow-up quality of life of survivors in mass poisoning outbreaks is not known. The objective of this is to study the impact of visual and central nervous system (CNS) sequelae of methanol poisoning on long-term health-related quality of life (QoL) of survivors, its clinical determinants, and dynamics. Materials and methods: A total of 54 patients with confirmed methanol poisoning (mean age 46.7 ± 13.4 years, 9 females) were examined consequently three times within six-year prospective cohort study and compared to 23 controls with the history of chronic alcohol abuse. The following tests were performed: SF-36 QoL questionnaire, visual evoked potentials (VEP) of optic nerve, ocular examination with retinal nerve fiber layer (RNFL) thickness measurement, brain magnetic resonance imaging (MRI), and biochemical and toxicological tests. Results: Acute methanol poisoning led to significant decrease in physical component summary (PCS) compared to PCS of age-adjusted controls (mean score with SD 46.8 ± 11.0 versus 52.3 ± 9.4 points; p  = .003). In 17/40 (42.5%) patients with three rounds of examination, signs of severe disability (≤30 points in at least one score) were present six years after discharge, with negative dynamics of PCS score during the observation period. The patients with abnormal RNFL thickness had lower PCS (mean difference 10.5 points; 95%CI 3.5–17.5, p  = .004) and mental component summary score (9.5 points; 95%CI 1.9–17.1, p  = .015) compared to the patients with normal RNFL. Signs of physical and mental adaptation to long-term visual sequelae were registered with gradual reduction of difference in most of physical and mental components scores compared to the patients with normal RNFL during six years of observation. Signs of hemorrhagic brain lesions were associated with permanent decrease of PCS score (mean difference 7.4 points; 95%CI 0.6–14.0; p  = .033), bodily pain (8.7 points; 95%CI 1.6–17.6; p  = .018), and social functioning (8.2 points; 95%CI 3.0–17.4; p  = .005) six years after discharge. No effect of type of antidote (fomepizole versus ethanol) and extracorporeal enhanced elimination modality (intermittent hemodialysis versus continuous renal replacement therapy) applied in hospital on long-term QoL was found (all p  > .05). Conclusion: Acute methanol poisoning was associated with a significant decrease of health-related quality of life of survivors persisting for at least six years after discharge. The more pronounced decrease in QoL scores was observed in the patients with hemorrhagic brain lesions and visual sequelae of poisoning with abnormal RNFL thickness.